(untitled) (Research, Society and Development, 2022)
According to market projections, livestock production systems will have, in 2050, the challenge of increasing their productivity by 60% while conserving natural resources. Rio Grande do Sul (RS), being an important livestock producer state of Brazil and for being historically linked to animal production, will have to implement managements that increase forage and animal productivity, especially in periods of food shortage. For this, the use of plant species adapted to climatic conditions of these periods can be a crucial tool for maintenance of livestock activities and ecosystem. In this context, this review aims to compile the main results of studies regarding consortium of ryegrass (main winter grass used in RS) with legumes, during forage shortage period in Pampa portion of RS, under forage and animal production context.